PENETAPAN KADAR FLAVONOID, FENOLIK DAN AKTIVITAS ANTIOKSIDAN EKSTRAK BUAH Tabernaemontana Macrocarpa JACK ASAL KALIMANTAN BARAT (DETERMINATION OF FLAVONOID, PHENOLIC, AND ANTIOXIDANT ACTIVITY OF Tabernaemontana Macrocarpa JACK FRUIT EXTRACT FROM WEST KALIMANTAN) - Andi Hairil Alimuddin; Rudiyansyah Rudiyansyah; Masriani Masriani (Indonesian Journal of Pure and Applied Chemistry, 2023)
Tabernaemontana macrocarpa Jack is one of the plants from the Tabernaemontana genus in the Apocynaceae family. Some compounds from the genus Tabernaemontana have shown interesting biological activities. Unfortunately, information about secondary metabolites and the bioactivity of T. macrocarpa Jack is limited. This study was conducted to determine the total phenolics and flavonoids contents of seeds flesh and fruit of T. montana together with their antioxidant activity. The seeds flesh and fruit of T. macrocarpa were extracted by maceration using methanol. Phytochemical tests showed that methanol extracts of seeds flesh and fruit contain alkaloids, flavonoids, and polyphenols. Total phenols and flavonoids were determined quantitatively by spectrometry and it showed that the seeds flesh contained more polyphenolics and flavonoids than the fruit. The results of the antioxidant activity showed that the seeds flesh and fruit extracts did not have antioxidant activity since their IC50 values were > 500 mg/L.